Ukuran, Usia dan Kinerja Reksa Dana Saham di Indonesia - Febrianti, Ni Putu Nadia Putri; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 33 No 4 (2023)DO - 10.24843/EJA.2023.v33.i04.p16, 2023)
This study aims to determine the effect of size and age on the performance of equity funds in Indonesia. The theory used in this research is the mutual fund theorem. The research was conducted on conventional and Sharia equity mutual funds registered with OJK for the 2015-2019 period. The data analysis technique used is multiple linear regression analysis. There were 59 equity funds that met the sampling criteria using a purposive sampling method consisting of 47 conventional equity funds and 12 Sharia-based equity funds. The results showed that the size and age of equity funds had no significant effect on their performance. The results of this study are consistent when using a sample of conventional and Islamic stock mutual funds. Keywords: Equity Mutual Funds; Size; Age; Performance; Mutual Fund Theorem